Prenatal Yoga as an Effort to Maintain Mental Health of Pregnant Women - Rury Narulita Sari; Nisa Ardhianingtyas; Wida Rahma Arwiyantasari; Lutfiah Indriani (Health Dynamics, 2025)
Background: Pregnancy brings both happiness and anxiety, as well as discomfort due to physical and psychological changes. As the pregnancy progresses, the discomfort increases, one of which is caused by the enlargement of the uterus leading to back pain. Excessive anxiety can affect mental health and may trigger depression during pregnancy. Prenatal yoga is one of the efforts that can be undertaken to overcome anxiety and discomfort in pregnant women. Prenatal yoga can help mothers feel more relaxed, thereby reducing anxiety. This study aims to explore in depth the effectiveness of implementing prenatal yoga in maintaining the mental health of pregnant women in the third trimester. Methods: Qualitative research methods with a phenomenological approach were used. The study was conducted at PMB Bd. Endah Wiendarti, SST Madiun in January 2025. The key informants were 10 pregnant women in the third trimester who participated in prenatal yoga, and the additional informants were midwives and companions of the pregnant women. Data collection techniques included in-depth interviews. Data analysis was carried out by categorizing data, presenting data, and drawing conclusions. Results: The results of the study show that prenatal yoga can maintain mental health, including helping mothers feel more relaxed, less anxious, and more prepared for childbirth. Conclusions: The conclusion of this study is that implementing prenatal yoga is beneficial in maintaining the mental health of pregnant women in the third trimester, helping them to be better prepared for childbirth. It is necessary to provide information about prenatal yoga from the beginning of pregnancy so that mothers can participate at the appropriate time to reduce discomfort in the third trimester.